Policy driven remote attestation - Gopalan,A; Gowadia,V; Scalavino,E; Lupu,E (2012)
Increasingly organisations need to exchange and share data amongst their employees as well as with other organisations. This data is often sensitive and/or confidential, and access to it needs to be protected. Architectures to protect disseminated data have been proposed earlier, but absence of a trusted enforcement point on the end-user machine undermines the system security. The reason being, that an adversary can modify critical software components. In this paper, we present a policy-driven approach that allows us to prove the integrity of a system and which decouples authorisation logic from remote attestation. © 2012 ICST Institute for Computer Science, Social Informatics and Telecommunications Engineering.